A new cultural adaptation of the University of Pennsylvania Smell Identification Test - Fornazieri, Marco Aurélio (2013)
OBJECTIVES: The University of Pennsylvania Smell Identification Test, a test of olfactory function that is widely used by otolaryngologists, geriatricians, and neurologists, has been translated into more than a dozen languages. In some instances, cultural and socioeconomic factors have necessitated changes in the odorant items or the response alternatives to make the test scores congruent with North American norms. The objective of this study was to compare the performance of Brazilian subjects on a new Portuguese language version of the University of Pennsylvania Smell Identification Test with their performance on an earlier Portuguese language version of the test, as well as to assess the influences of gender, age, ethnicity, and economic status on the test scores. METHODS: Based on pilot data, several response alternatives of the earlier Portuguese language version of the test were altered in an effort to improve test performance. Forty-nine healthy Brazilian volunteers, who represented several economic classes, were tested. The test scores of the study cohort who received the newer version of the test were compared with those of a group of 25 subjects who received the earlier version of the test. RESULTS: The mean score for the new version [35 (2.1)] was significantly (p = 0.002) higher than that for the earlier version [32.5 (3.5)]. Although no apparent influence of socioeconomic status was observed, the female participants outperformed the male participants in the current subject cohort. CONCLUSION: The changes made in the new cultural adaptation of the Portuguese version of the University of Pennsylvania Smell Identification Test were effective in increasing the average test scores of the participants. Overall, the female subjects outperformed the male subjects on the test.